Evaluation of Poverty Alleviation Policies in Enrekang Regency - Zainal, Henni; Sose, Andi Tenry (Universitas Negeri Makassar, 2025)
This study aims to analyze the dynamics of poverty in Enrekang Regency over the past 10 years, focusing on factors influencing fluctuations in poverty levels and the effectiveness of implemented poverty alleviation programs. This study uses a quantitative approach with secondary data analysis methods obtained from the Central Statistics Agency (BPS) and various relevant government reports. In addition, qualitative analysis was also conducted through interviews with local policymakers to understand the policy context and its implementation. The results show that despite a gradual decline in poverty levels, disparities between regions remain significant, particularly between rural and urban areas. Factors such as limited access to education, inadequate infrastructure, and dependence on the agricultural sector are the main causes that slow down poverty reduction. On the other hand, social assistance programs and community-based economic development have had a positive impact, although not optimal. This study concludes that to achieve more significant poverty reduction, more focused efforts are needed on improving the quality of human resources, developing infrastructure, and diversifying the local economy. Policy recommendations include increasing access to education, strengthening the non-agricultural sector, and optimizing more targeted social assistance programs.